Combine the daylight and artificial light based fuzzy logic - Quyền , Huy Ánh; Lê , Tấn Thanh Tùng; Phạm , Thị Minh Thủy (Journal of Technical Education Science, 2013)
The paper present a strategy of artificial lighting control to respond the natural state of daylight based on fuzzy logic control. After building the fuzzy logic controller, simulation results using Matlab program in two scenarios are built. For each scenario, the survey simulation output responses the whole range of daylight corresponding to each of input statement. The simulation results show that the output of the fuzzy controller is good responsive the equilibrium when the input illumination changes, while the 4 zones scenario have more sensitive result than the 3 zones scenario.